Setting things straight in 'The twist-bend nematic: a case of mistaken identity'. Issue 13 (20th October 2020) - Dozov, Ivan; Luckhurst, Geoffrey R.
ABSTRACT: Stimulated by the paper that precedes this, our aim is to correct an error made concerning the twist-bend nematic phase and to place its development, both theoretical and experimental, in their proper context. The prediction starts with R.B.Meyer in 1973 but then jumps to 2001 and a different direction with I. Dozov and to 2002 with R. Memmer. There was then a gap until 2011 when a team of thirteen European scientists, while studying a liquid crystal dimer formed from achiral bent molecules, identified a nematic phase as the missing twist-bend nematic. This was based on a detailed study of its defining characteristics such as the chirality of the phase and its helicoidal structure with its degenerate handedness. This discovery proved to be of considerable interest and has prompted numerous investigations resulting in the discovery of many other mesogens forming the twist-bend nematic phase. However, as we shall see this view has not been universally shared; indeed, amongst others, Samulski, Vanakaras and Photinos claim that cyanobiphenyl mesogens instead of producing the NTB nematic, form the polar twisted phase, NPT so that the twist-bend nematic has yet to be discovered. It is this error that we shall correct.The Doubly Degenerate Heliconical Structure GRAPHICAL ABSTRACT: uf0001